Ruling peacefully: Cardinal Ercole Gonzaga and patrician reform in sixteenth-century Italy - Murphy, Paul V. (Catholic Univ. of America Press, 2007)
The intellectual and cultural formation of a cardinal -- Gonzaga, reform, and the office of Bishop -- Reform in the Diocese of Mantua -- Gonzaga and the "Spirituali" -- The regency in Mantua -- Gonzaga and the Council of Trent